Between borders and substances: Body packer cases among refugees in Van, Türkiye - Tatlı, Mehmet; Sutaşır, Mehmet Necmeddin (Addicta: The Turkish Journal on Addictions, 2026)
Van, Türkiye’s eastern border province, is a major transit corridor for irregular migrants and lies on the Balkan route for drug trafficking. This study describes the clinical and radiological features of body packer cases presenting to an emergency department in this critical border region. This retrospective case series included all 13 confirmed body packer patients who presented to the University of Health Sciences, Van Training and Research Hospital Emergency Department between January 2021 and November 2025. Data on demographics, clinical presentation, imaging findings, and management were extracted from medical records. Eleven patients (84.6%) were refugees or irregular migrants; all 13 were brought by law enforcement, with no voluntary self-presentations. The median age was 33 years, and 12 were male. The concealed substances were predominantly methamphetamines (69.2%), followed by opioids (15.4%) and cocaine (15.4%). Seven patients (53.8%) were asymptomatic. CT imaging, used in all cases, showed a 100% detection rate. A key finding was the observation of two patients with rectal packet clustering and marked bladder distension, both reporting deliberate avoidance of defecation and urination—a behavioral cue for high-risk screening. The single female patient had multiluminal concealment (rectal and vaginal). No toxicity or mortality occurred; median hospital stay was 3 days. Body packing among migrants in Van is an under-recognized phenomenon at the intersection of migration, trafficking, and substance use vulnerability. The small number of detected cases, all law-enforcement-driven, suggests a significant underestimation of the true burden. The predominance of methamphetamines suggests a significant stimulant trafficking trend. Border-region emergency departments must implement risk-based screening strategies, integrate addiction services, and adopt trauma-informed care frameworks to address the complex needs of this vulnerable population.
Keywords: methamphetamine; body packing; drug trafficking; migration; refugees; emergency management